HIV testing rate and seroprevalence among people attending a mental health clinic in rural Malawi - Lommerse, Kinke (Department of Paediatrics and Child Health, 2015)
This study was undertaken to assess HIV-prevalence, uptake of HIV-care, general clinical characteristics and risk factors among a population visiting a mental health clinic in a rural Malawian district hospital.